Vak learning style in four Arabic language skills in International Islamic University College Selangor IIUCS - Rosnan, Farah Nur-Rashida; Abdul Jabar, Mohd Azidan; Mustafa, Nik Farhan (Academic Industry Networks, 2021)
Learning styleis an important element and have a big impact in the world ofeducation.Hence, this study emphasizes the aspects ofVisual, Auditory, and Kinesthetic (VAK)learning styleson4Arabic Language Skills (ALS). This researchis a pilot study conductedat the Selangor International Islamic University College (KUIS).Researchers used the questionnaire adapted from the questionnaire in visual, auditory, and kinesthetic learning styles (VAK).A total of39Bachelor of Arabic as a Second Language students comprising two classes involved as respondents in this study.Descriptive statistics were used to obtain information in frequency and percentages of student profile variablesandstudentbackground.Frequency statistics are used forvisual learning styles, auditory learning styles, and Kinesthetic learning styles.The results showed that students were more likely to useKinestheticlearning stylesrather than usingVisualandAuditorylearning styles.